Synergy of arsenic with smoking in causing cardiovascular disease mortality: A cohort study with 27 follow-up years in China - Jia, Xin-Hua; Su, Zheng; Zhao, Fang-Hui; Zhou, Qing-Hua; Fan, Ya-Guang; Qiao, You-Lin (Frontiers in Public Health, 2022)
(1) Background: To explore the patterns of the exposure-response relationship between arsenic exposure and cardiovascular disease (CVD) mortality and investigate the effect of cigarette smoking on the association. (2) Methods: 7735 tin miners with at least 10 years of arsenic exposure were enrolled since 1992 and followed up for 27 years. Each individual's air arsenic exposure at workplace was calculated by time weighted average arsenic concentration x exposure months. Detailed information on smoking was collected at baseline, and information on smoking status was collected for five consecutive years from 1992 to 1996. (3) Results: A total of 1046 cardiovascular disease deaths occurred in this cohort over 142,287.7 person-years of follow up. We firstly reported that for equal cumulative exposure, participants exposed to higher concentrations over shorter duration had a higher risk of CVD mortality than those exposed to lower concentration over longer duration. The HR and 95% CI were 1.38 (95%CI: 1.03 - 1.85) in participants exposed to arsenic concentration (45.5 - 99.5 mg/m3), 1.29 (95%CI: 1.02 - 1.67) in 99.5 - 361.0 mg/m3. Further, participants with age at first exposure < 18 years had a significantly higher risk of morality from disease of cardiovascular, cerebrovascular and heart than those with ≥ 18 years. Finally, all synergy indices were greater than 1 (range, 1.11-2.39), indicating that the joint effect of arsenic exposure and cigarette smoking on CVD mortality was greater than the sum of their individual effect. (4) Conclusions: Exposure to air arsenic at workplace is adversely associated with mortality from cardiovascular disease, especially among smokers younger than 18 years and smokers.